2018
DOI: 10.2139/ssrn.3187331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Government Spending on Employment: Evidence from Winners and Runners-Up in Procurement Auctions

Abstract: To estimate demand for labor, we use a combination of detailed employment data and the outcomes of procurement auctions, and compare the employment of the winner of an auction with the employment of the second ranked firm (i.e. the runner-up firm). Assuming similar ex-ante winning probabilities for both firms, we may view winning an auction as an exogenous shock to a firm's production and its demand for labor. We utilize daily data from almost 900 construction firms and about 3,000 auctions in Austria in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The second strand of literature concerns the impact of public procurement on rms' performance. The literature has shown that demand shocks, stemming from public procurement, increase rm growth measured using revenue and employment (Ferraz et al, 2015;Weichselbaumer et al, 2018;Hoekman and Sanlippo, 2018). This eect is particularly prominent for small rms, as public procurement enables them to relax their nancial constraints (Lee, 2017;Fadic, 2020).…”
Section: Related Literature and Contributionmentioning
confidence: 99%
“…The second strand of literature concerns the impact of public procurement on rms' performance. The literature has shown that demand shocks, stemming from public procurement, increase rm growth measured using revenue and employment (Ferraz et al, 2015;Weichselbaumer et al, 2018;Hoekman and Sanlippo, 2018). This eect is particularly prominent for small rms, as public procurement enables them to relax their nancial constraints (Lee, 2017;Fadic, 2020).…”
Section: Related Literature and Contributionmentioning
confidence: 99%